ANALISIS PENGARUH METODE TIMES GAME TOURNAMENT TERHADAP KEMAMPUAN NUMERASI SISWA KELAS IV SEKOLAH DASAR NEGERI SIDOREJO 02 - Siti Aisyah; I Made Ratih Rosanawati (STKIP Subang, 2026)
The purpose of this study was to determine the effect of the Times Game Tournament Method on the Numeracy Skills of Fourth-Grade Students at Sidorejo 02 Public Elementary School. Data collection methods were conducted through tests, observations, and documentation. The population in this study was all fourth-grade students at Sidorejo 02 Public Elementary School, totaling 13 students.This study employed a quantitative method with a quasi-experimental design in the form of a one-group pretest–posttest design. The subjects in this study were all fourth-grade students at Sidorejo 02 Public Elementary School. Data were collected through numeracy ability tests administered before (pretest) and after (posttest) the implementation of the Times Game Tournament learning model. Data analysis was carried out with prerequisite tests to ensure normality and hypothesis testing through paired sample t-tests. The results showed that the average value of students' numeracy skills increased from a pretest value of 58.84 to a posttest value of 81.92. The results of the paired t-test showed a significance value (Sig. 0.000 < 0.05), which means there was a significant difference between the pretest and posttest scores. Thus, it can be concluded that the application of the Times Game Tournament learning model has a positive effect on improving the numeracy skills of fourth-grade students at Sidorejo 02 Elementary School.